(untitled) (International Journal of Engineering and Computer Science, 2015)
In today’s world, safety and security are the major aspects that are confronted by any individual. The existing systems in the present scenario are not efficient enough to provide necessary security. We implement a system "cab tracking and personal security system" is an android application. Android is a new generation of smart mobile phone platform launched by google. Cab tracking and personal security system enables the server (company) to track the employees who opt for cab services as well as helps the employee to retrieve the information about their current location and offers possible services according to the need. With the help of GPS in phones and through web services using GPRS, Location based Services are implemented on android smart phones to provide services like advising clients with routing information, help them finding nearby Emergency Services.